2005
DOI: 10.1107/s1744309105007463
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the three-dimensional structure ofSalmonella typhimuriumuridine phosphorylase in the crystalline state

Abstract: PDB Reference: StUPh, 1sj9, r1sj9sf.Uridine phosphorylase (UPh) catalyzes the phosphorolytic cleavage of the C-N glycosidic bond of uridine to ribose 1-phosphate and uracil in the pyrimidine-salvage pathway. The crystal structure of the Salmonella typhimurium uridine phosphorylase (StUPh) has been determined at 2.5 Å resolution and refined to an R factor of 22.1% and an R free of 27.9%. The hexameric StUPh displays 32 point-group symmetry and utilizes both twofold and threefold non-crystallographic axes. A pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…The structure of Salmonella typhimurium UP is very similar to that of EcUP (5). The bacterial enzyme exists as a hexamer comprised of six identical subunits.…”
mentioning
confidence: 85%
“…The structure of Salmonella typhimurium UP is very similar to that of EcUP (5). The bacterial enzyme exists as a hexamer comprised of six identical subunits.…”
mentioning
confidence: 85%
“…Our understanding of the fundamental catalytic mechanisms underlying UPP activity was founded on the structural analysis of bacterial UPPs, first with E. coli UPP (Morgunova et al, 1995; Burling et al, 2003; Caradoc-Davies et al, 2004; Bu et al, 2005) followed by research on the closely-related S. typhimurium homologue (Dontsova et al, 2005; Lashkov et al, 2009, 2010). Only recently have multiple structures of the human enzyme, hUPP1 (Roosild et al, 2009; Roosild and Castronovo, 2010), its bovine homologue, bUPP1 (Paul et al, 2010), and a UPP from the parasitic protozoa, Trypanosoma brucei (Larson et al, 2010), revealed key differences between prokaryotic and eukaryotic variations of this enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The space group and unit-cell parameters of these crystals (Table 1) are strikingly different from those of the native (Dontsova et al, 2005; space group P6 1 ; a = 91.37, c = 266.38 Å ), despite the fact that the native crystals were obtained under similar conditions with a reservoir solution consisting of 100 mM sodium acetate pH 5.0, 7%(w/v) PEG 8000. We anticipate that the structure determination in progress will reveal that these are crystals of the complex of StUPh with ANU.…”
Section: Resultsmentioning
confidence: 97%
“…The structure was solved by molecular replacement. The previously reported hexamer structure of S. typhimurium uridine phosphorylase at 2.5 Å resolution (Dontsova et al, 2005; PDB code 1sj9) was used as the starting model. The amino-acid sequence was obtained from the SWISS-PROT database (CAA74658).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation